Meningkatkan Kompetensi Guru dengan Pemahaman Literasi Hukum di SMPN 4 Tambun Selatan - Prawitasari, Nining Yurista; Sayudi, Akbar; Apriani, Erna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Quality education not only involves mastery of academic material but also understanding the norms, laws, and ethics that prevail in society. One important factor in achieving this goal is the role of teachers as agents of change in educating the future generation. Community service discusses the importance of improving teachers' competencies through understanding legal literacy, as well as its impact on better classroom management and teaching. Legal literacy has become a crucial skill for teachers to ensure that they can manage legal issues in the educational environment more effectively. This service also discusses various strategies and approaches to enhance legal literacy among educators.